2006
DOI: 10.1002/ijc.21844
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of squamous carcinoma in mice with a vaccine enriched for cells that induce immunity to squamous carcinoma—A new vaccination strategy

Abstract: We report a new vaccination strategy for squamous cell carcinoma (SCC). The vaccine was prepared by transfer of unfractionated DNA-fragments (25 kb) from squamous carcinoma cells (KLN205, DBA/2 origin (H-2 d )) into LM mouse fibroblasts (C3H/ He origin; H-2 k ), a highly immunogenic cell line. To enhance their nonspecific immunogenic properties, the fibroblasts were modified before DNA transfer to secrete IL-2 and to express additional allogeneic MHC class I determinants. As the transferred DNA integrates into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…Immunization of tumor-bearing mice with the DNAbased vaccine resulted in the induction of cell mediated immunity directed toward the type of tumor from which the DNA was obtained, and prolongation of survival, consistent with the expression of an array of TAA by the transfected cells. This was the case for mice with melanoma, squamous cell carcinoma and in mice with breast cancer [Chopra et al, 2006;deZoeten et al, 2002;Lichtor et al, 2008]. Multiple undefined genes specifying TAA that characterize the malignant cell population were expressed by cells that took up DNA from the tumor.…”
Section: Discussionmentioning
confidence: 96%
“…Immunization of tumor-bearing mice with the DNAbased vaccine resulted in the induction of cell mediated immunity directed toward the type of tumor from which the DNA was obtained, and prolongation of survival, consistent with the expression of an array of TAA by the transfected cells. This was the case for mice with melanoma, squamous cell carcinoma and in mice with breast cancer [Chopra et al, 2006;deZoeten et al, 2002;Lichtor et al, 2008]. Multiple undefined genes specifying TAA that characterize the malignant cell population were expressed by cells that took up DNA from the tumor.…”
Section: Discussionmentioning
confidence: 96%
“…18 The A 260 /A 280 ratio of the isolated DNA was 41.8 in each instance. The molecular size of the extracted DNA was approximately 25 kb, as determined by agarose gel electrophoresis.…”
Section: Methodsmentioning
confidence: 96%
“…18 An analysis by enzyme-linked immunosorbent assay of the culture supernatants of LM-IL-2 cells indicated that 10 6 transduced cells formed 196 pg IL-2/ml/10 6 cells/48 h.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations